A screening gate to prevent entry of mobile telephone handsets in the speaking - Hanada, E.
Electromagnetic interference to electronic equipment by mobile telephone handsets is well known. We present an automatic screening gate that detects concealed mobile telephone handsets and classifies them by type. The screening method used in the gate does not require any additions to or reconstruction of mobile telephone systems.
Keywords: Automatic screening gate; Electromagnetic interference; Handset entry prevention; Mobile telephone handsets; Prohibited areas; Restricted areas; Telephone speaking mode; Telephone standby mode